The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/3871496
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Odontogenic Differentiation from Human Dental Pulp Stem Cells Using TMT-Based Proteomic Analysis

Abstract: Background. The repair of dental pulp injury relies on the odontogenic differentiation of dental pulp stem cells (DPSCs). To better understand the odontogenic differentiation of DPSCs and identify proteins involved in this process, tandem mass tags (TMTs) coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS) were applied to compare the proteomic profiles of induced and control DPSCs. Methods. The proteins expressed during osteogenic differentiation of human DPSCs were profiled using the TMT me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In PPI networks, proteins that have direct interaction with several other proteins are called hub proteins (hub nodes). Proteins with more interaction partners may become targets for follow-up investigation [107]. In this study, the constructed PPI network (25 nodes and 149 edges) demonstrated that C3, C5, CCL5, CR1, CXCL8, IL10, IL-4 and CXCR1 were the hub proteins (nodes).…”
Section: Discussionmentioning
confidence: 74%
“…In PPI networks, proteins that have direct interaction with several other proteins are called hub proteins (hub nodes). Proteins with more interaction partners may become targets for follow-up investigation [107]. In this study, the constructed PPI network (25 nodes and 149 edges) demonstrated that C3, C5, CCL5, CR1, CXCL8, IL10, IL-4 and CXCR1 were the hub proteins (nodes).…”
Section: Discussionmentioning
confidence: 74%
“…The continuous search for alternatives other than the present antibiofilm agents became a required demand because of the high economic cost of the present used synesthetic antibiofilm agents and the possibility of developing serious side effects upon their long term administration (Qiu et al 2020 ). The use of herbal products has a low-cost value, least probability of developing major side effects comparable to the conventional antibiofilm agents that are available.…”
Section: Discussionmentioning
confidence: 99%
“…In PPI networks, proteins that have direct interaction with several other proteins are called hub proteins (hub nodes). Proteins with more interaction partners may become targets for follow-up investigation [ 105 ]. In this study, the constructed PPI network (25 nodes and 149 edges) demonstrated that C3, C5, CCL5, CR1, CXCL8, IL10, IL-4 and CXCR1 were the hub proteins (nodes).…”
Section: Discussionmentioning
confidence: 99%